Supercontinuum generation using a passive mode-locked stretched-pulse bismuth-based erbium-doped fiber laser - Shahabuddin, N.S.; Awang, N.A.; Ahmad, Harith; Arof, Hamzah; Dimyati, K.; Yusoff, Z.; Harun, Sulaiman Wadi (Elsevier, 2012)
Supercontinuum (SC) generation in photonic crystal fiber (PCF) is demonstrated using an amplified picosecond stretched-pulses from a passive mode-locked Bismuth-based Erbium-doped fiber laser (Bi-EDFL). The Bi-EDFL employs of a piece of a highly nonlinear 49 cm long Bismuth-based Erbium-doped fiber (Bi-EDF), an optical isolator and a polarization controller in a cavity to generate a mode-locked stretched-pulse via a nonlinear polarization rotation technique. It operates at 1560 nm with a repetition rate of 42 MHz and a pulse width of 131 fs. The SC lights, which extends from 1250 nm to 1910 nm as well as in the visible green wavelength region are obtained with a 100 m long PCF and the amplified pump power of 30 dBm.